Adoptinge educational robotics to enhance undergraduate students’ self-efficacy levels of computational thinking - Arıstawatı, Feri Ardiana; Budıyanto, Cucuk; Yuana, Rosihan Ari (Journal of Turkish Science Education, 2018)
Computational Thinking (CT) skill, as an essential 21st-century skill, is an important problem-solving and survival abilities in the era of disruption. Universal principles generating a pattern of abstraction develop step-by-step troubleshooting instructions in solving similar problems, perceiving similarities/differences between the patterns, and making a complex problem solvable. The skill could be applied to various engineering fields by emphasising efficiency, accuracy, and capability of problem-solving. Recently, robot enthusiasts in Science, Technology, Engineering and Math (STEM) learning that involves ‘assembling, programming and testing’ activities, underscore CT skills. This research explores the CT pattern along with participants-developed robotics activities.